Randomized double-blinded placebo-controlled trial of hydroxychloroquine with or without azithromycin for virologic cure of non-severe Covid-19. (December 2020) - Omrani, Ali S.; Pathan, Sameer A.; Thomas, Sarah A.; Harris, Tim R.E.; Coyle, Peter V.; Thomas, Caroline E.; Qureshi, Isma; Bhutta, Zain A.; Mawlawi, Naema Al; Kahlout, Reham Al; Elmalik, Ashraf; Azad, Aftab M.; et al.
Abstract: Background: Hydroxychloroquine (HC) ± azithromycin (AZ) is widely used for Covid-19. The Qatar Prospective RCT of Expediting Coronavirus Tapering (Q-PROTECT) aimed to assess virologic cure rates of HC±AZ in cases of low-acuity Covid-19. Methods: Q-PROTECT employed a prospective, placebo-controlled design with blinded randomization to three parallel arms: placebo, oral HC (600 mg daily for one week), or oral HC plus oral AZ (500 mg day one, 250 mg daily on days two through five). At enrollment, non-hospitalized participants had mild or no symptoms and were within a day of Covid-19 positivity by polymerase chain reaction (PCR). After six days, intent-to-treat (ITT) analysis of the primary endpoint of virologic cure was assessed using binomial exact 95% confidence intervals (CIs) and χ 2 testing. (ClinicalTrials.gov NCT04349592, trial status closed to new participants.) Findings: The study enrolled 456 participants (152 in each of three groups: HC+AZ, HC, placebo) between 13 April and 1 August 2020. HC+AZ, HC, and placebo groups had 6 (3·9%), 7 (4·6%), and 9 (5·9%) participants go off study medications before completing the medication course ( p  = 0·716). Day six PCR results were available for all 152 HC+AZ participants, 149/152 (98·0%) HC participants, and 147/152 (96·7%) placebo participants. Day six ITT analysis found no difference ( p  = 0·821) in groups' proportions achieving virologic cure: HC+AZ 16/152 (10·5%), HC 19/149 (12·8%), placebo 18/147 (12·2%). Day 14 assessment also showed no association ( p  = 0·072) between study group and viral cure: HC+AZ 30/149 (20·1%, ), HC 42/146 (28·8%), placebo 45/143 (31·5%). There were no serious adverse events. Interpretation: HC±AZ does not facilitate virologic cure in patients with mild or asymptomatic Covid-19. Funding: The study was supported by internal institutional funds of the Hamad Medical Corporation (government health service of the State of Qatar).